Memory within and without the photographic frame: Wadad Halwani's The Last Picture… While Crossing. (June 2019) - Nikro, Norman Saadi
Wadad Halwani's short documentary film, The Last Picture…While Crossing (2009), is in the main about the late Odette Salem, whose two children were disappeared in September 1985, during the civil war in Lebanon (1975-1990). This essay discusses how Halwani adapts photographs and previously made video footage to situate Salem as a site of memory. While the film constitutes a memorial practice to tell a story of Salem and her activist milieu, it works to situate memory of her plight as an ethical modality of address and response. In doing so, the film exposes a public audience, both actual and potential, to Salem's and Halwani's circumstances and their arduous efforts in engaging their circumstances. The argument foregrounds memory as a circumstantial tension between the significance and resonance of photographs, in respect to circulations of photographic reproductions and exhibitions as modalities of public exposure.